4D printing: Pragmatic progression in biofabrication. (15th April 2022) - Sonatkar, Janhavi; Kandasubramanian, Balasubramanian; Ismail, Sikiru Oluwarotimi
Graphical abstract: Abstract: Progress in three-dimensional (3D) printing of shape memory polymers (SMPs) has produced dynamic and 3D-printed assemblies that can be shaped fast and modified for specific and multifaceted designs. Technology, biochemistry, medicine, computer science and biomaterials are among the areas of specialization, where 3D and four-dimensional (4D) printing techniques have penetrated to herald the next generation of manufacturing processes. Through layer-by-layer addition of diverse materials, 3D printing allows intricate assemblies with high precision. In today's additive manufacturing (AM), 4D printing encapsulates additional magnitude, which is time. Intelligent materials that deform or change color emit an electrical current that becomes bioactive or performs a specific function in response to an external stimulus overlay to manufacture dynamic 3D structures, through a technique known as 4D printing. With this modern dimension, 3D-printed substances can alter their form by themselves, concluding the impact of peripheral stimuli, such as light, heat, electricity and magnetic field, among others. For instance, the cartilage healing and physiological maturation techniques promote bone marrow to differentiate into osteoblasts. SMPs have also been developed as tools and stages for biomedical study. Summarily, this study focuses on a systematic compendious review of 3D and 4D printing techniques and their implications in biomedical techniques. Specific technologies intend to focus on such intelligent materials, and therefore it is essential to modernize the current voxel-based analysis, design methodology and explore effective printable technologies for fabricating organic components. Health professionals will benefit from 4D printing, especially in areas where 3D printing is not available. 4D printing allows for the construction of a three-dimensional building by layering smart material and using computer-operated computer-aided design (CAD) data. It presents a new level of translation over time, in which elements like heat, moisture, and duration affect printed materials. This breakthrough has the potential to make a difference in the health sector, especially when smarter and more sophisticated surgical implants, equipment, and technology become available. 4D printing methods might now be used by medical researchers to improve quality of care.